2021
DOI: 10.1371/journal.pone.0253806
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of sludge dewatering for single- and double-drainage conditions with a vacuum negative pressure load at the bottom

Abstract: The moisture content of municipal sludge is relatively high, which increases the cost of sludge transportation and treatment. To reduce the volume of the sludge, sludge dewatering is needed. This paper proposes the theory of sludge dewatering and facilitates efficient and economical technology of sludge dewatering. Sludge dewatering tests were carried out by using homemade rapid sludge dewatering devices. There were two groups of tests with single- and double-drainage conditions, and all test runs were loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In wet air oxidation, insoluble organics substances are first converted into simple soluble organics by dissolution, and then further oxidized to carbon dioxide, water, and readily biodegradable intermediates [ 60 , 61 ]. The study found that the temperature in WAO had a significant influence on the dewatering performance of the sludge, and the dewatering performance was significantly improved at high temperature.…”
Section: Application Of Other Technologies In Sludge Dewateringmentioning
confidence: 99%
“…In wet air oxidation, insoluble organics substances are first converted into simple soluble organics by dissolution, and then further oxidized to carbon dioxide, water, and readily biodegradable intermediates [ 60 , 61 ]. The study found that the temperature in WAO had a significant influence on the dewatering performance of the sludge, and the dewatering performance was significantly improved at high temperature.…”
Section: Application Of Other Technologies In Sludge Dewateringmentioning
confidence: 99%
“…In practical engineering, sludge dewatering without conditioning is very poor [5]. The more difficult moisture to remove in mechanical sludge dewatering is bound to water that cannot be removed by simple mechanical pressure [6]. In China's municipal sewage treatment plants, inorganic polymeric coagulants such as polymeric aluminum chloride (PAC) and organic polymeric flocculants such as polyacrylamide (PAM) are generally added to thickened sludge for sludge conditioning prior to dewatering.…”
Section: Introductionmentioning
confidence: 99%